2023
DOI: 10.1002/pssr.202200435
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Photoconductivity and Optical Properties in Oxygen‐Containing Yttrium Hydride Thin Films

Abstract: Oxygen‐containing yttrium hydride (YHO), primarily known for its photochromic properties, simultaneously shows a photoconductive response. Polycrystalline YHO thin films are deposited by reactive magnetron sputtering onto glass substrates and their optical and electrical properties are correlated under illumination with light. While photoconductivity is found in a broader range of compositions than photochromism, maximum photoconductive response is found for samples exhibiting photochromism. This photoconducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Thin films of YHO are typically produced by either reactive magnetron sputtering or e – beam evaporation of yttrium dihydride followed by oxidation and they show photochromic properties in a range of chemical compositions with the oxygen to yttrium ratio δ of 0.5 < δ < 1.5 . Moreover, photochromism is commonly coupled to photoconductivity, , even though the latter one is also found in YHO films with δ < 0.5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin films of YHO are typically produced by either reactive magnetron sputtering or e – beam evaporation of yttrium dihydride followed by oxidation and they show photochromic properties in a range of chemical compositions with the oxygen to yttrium ratio δ of 0.5 < δ < 1.5 . Moreover, photochromism is commonly coupled to photoconductivity, , even though the latter one is also found in YHO films with δ < 0.5 …”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, photochromism is commonly coupled to photoconductivity, 3,10 even though the latter one is also found in YHO films with δ < 0.5. 11 While the dependency of the photochromic behavior of YHO on chemical composition, thickness, and environment have been studied extensively, 9,12 the fundamental mechanism underlying the photochromic effect remains debated. For GdHO thin films, Hans et al showed a dual-phase nature of the material and proposed a photoinduced transfer of hydrogen between the two phases linked to the residual stress of several GPa as a mechanism of the photochromic behavior.…”
Section: Introductionmentioning
confidence: 99%